Reconsidering the user experience in the age of connected devices - Charlier, Martin; Lui, Alfred; Rowland, Claire; Goodman, Elizabeth; Light, Ann (O'Reilly Media, Inc., 2016)
The Internet of Things represents an enormous design challenge, as our expectations for physical-world objects are quite different than for digital-only devices. This lesson introduces how to approach UX for IoT, considerations for device interoperability, and opportunities and challenges for leveraging the data produced by those devices. Why is it important? IoT requires special design considerations, since the user experience is cross-platform and takes place across diverse physical contexts, with different devices. It's no longer enough to think about screen-based interfaces; we have to consider the entire system of networked devices and data flows. What you'll learn--and how you can apply it You'll learn how to reconsider the user experience (UX) in the context of IoT. Explore factors in device interoperability, and how they affect systems design and the end user. You'll learn about opportunities and challenges around the data produced by connected devices and their interactions. This lesson is for you because ... You're a designer starting to work with networked devices You're a product designer or engineer interested in improving the user experience of your products Prerequisites Familiarity with basic principles of user experience design Materials or downloads needed in advance None